2017
DOI: 10.1002/mnfr.201600895
|View full text |Cite
|
Sign up to set email alerts
|

In vivo metabolomic interpretation of the anti‐obesity effects of hyacinth bean (Dolichos lablab L.) administration in high‐fat diet mice

Abstract: A lower dose of hyacinth bean resulted in similar anti-obesity effects as milk thistle, as confirmed by both clinical and metabolomics analyses. Equivocally, we conjecture that hyacinth bean could be used as a potent anti-obesity herbal functional food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
(41 reference statements)
0
11
0
5
Order By: Relevance
“…Discriminative variables were selected based on variable importance in the projection (VIP) value of the PLS-DA. The selected metabolites obtained from GC-TOF-MS and UHPLC-LTQ-Orbitrap-MS were tentatively identified based on various data comparing their retention time (min), mass spectrum (m/z), an MS n fragment pattern with those for standard compounds analyzed under identical conditions, and various, available databases including the Human Metabolome Database (HMDB, http://www.hmdb.ca/), the National Institute of Standards and Technology (NIST) database (Version 2.0, 2001, FairCom, Gaithersburg, MD, USA), Wiley 9, in house libraries, and published papers [51]. Significant differences were evaluated by analysis of variance (ANOVA) and Student' t-test coupled with the Pearson's correlation coefficient between metabolites and the corresponding phenotype using Predictive Analytics SoftWare (PASW) Statistics 18 software (SPSS Inc., Chicago, IL, USA).…”
Section: Discussionmentioning
confidence: 99%
“…Discriminative variables were selected based on variable importance in the projection (VIP) value of the PLS-DA. The selected metabolites obtained from GC-TOF-MS and UHPLC-LTQ-Orbitrap-MS were tentatively identified based on various data comparing their retention time (min), mass spectrum (m/z), an MS n fragment pattern with those for standard compounds analyzed under identical conditions, and various, available databases including the Human Metabolome Database (HMDB, http://www.hmdb.ca/), the National Institute of Standards and Technology (NIST) database (Version 2.0, 2001, FairCom, Gaithersburg, MD, USA), Wiley 9, in house libraries, and published papers [51]. Significant differences were evaluated by analysis of variance (ANOVA) and Student' t-test coupled with the Pearson's correlation coefficient between metabolites and the corresponding phenotype using Predictive Analytics SoftWare (PASW) Statistics 18 software (SPSS Inc., Chicago, IL, USA).…”
Section: Discussionmentioning
confidence: 99%
“…It demonstrated that HEE could lower the risk of arteriosclerosis. Because lipids are valuable source and stores of metabolic energy, level changes of metabolites related to lipid in adipose have been regarded as the indicators of obesity‐related disorders (Green, Kwok & Durrington, ; Kim et al.,; Laaksonen et al., ; Suh et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…After centrifugation (12,578 g , 4°C, 10 min), the supernatant was filtered using a 0.2-μm PTFE filter, and dried using a speed vacuum concentrator. The dried extracts were re-dissolved with 80% methanol (10mg/ml) for UPLC-Q-TOF-MS analysis under previously described analytical conditions [ 16 ]. For GC-TOF-MS analysis, dried samples were oximated with 50 μL of methoxyamine hydrochloride (20 mg/mL in pyridine) for 90 min at 30°C, and silylated with 50 μL of MSTFA for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%